Competition and Marketing Challenges in the USA Market for Indian Granite Exporters - Mishra, Mahima; Prakash, Anand (Indian Journal of Marketing, 2015)
Purpose: The purpose of this paper was to study competition and marketing challenges that granite exporters from India faced in the USA market for apprehending both the domestic and the export markets. Design: This paper is descriptive in nature, and it applied snowball sampling method to report a survey of 82 completed responses about the marketing challenges faced by Indian granite traders for the domestic market and the USA market. It used published data of granite businesses since the year 2004 to study trends for understanding competition. Findings: The paper contemplated that with growing demand of granite both for the domestic market and the international market, especially the USA, India needs a paradigm shift in marketing strategy for granite. Key challenges were identified for driving success both in the domestic market and the USA market. Practical Implications: The paper provided an insight about the dynamics at domestic as well as inter-country level for comparing competitive standing alongside the review of literature. It highlighted key challenges in the domestic market and in the USA market for use by policy makers, exporters, and academicians. Originality/Value: The paper incorporated competition and marketing challenges of the granite business for generating ideas that could be used as basis for a policy action plan.